Estimasi bidang gelincir menggunakan metode geolistrik di Kelurahan Balai Gadang Kecamatan Koto Tangah (The estimation of the slip area uses the geoelectric method in the Balai Gadang Village, Koto Tangah District ) - Desi Anriani; - Akmam; Harman Amir (Department of Physics – Universitas Negeri Padang UNP, 2018)
Landslides have the potential to occur in the Kelurahan Balai Gadang of padang. The landslide should be minimized by knowing slip surface. For this reason, the aims of this research was to find the location of the area which the potential for landslide occurs. The research is descriptive using method Geolistrik Resistivity Schlumberger configuration. Data were collected by Automatic Resistivity multielectrode in 4 lines. The interpretion of the data used Smothness-Constarint Least Square inversion with the help of Res2dinv software. Based on the structure of the obtained rocks, it is estimated of slip surface and depth of slip surface. The results showed that the slip surface found at coordinates one, two, and four with resistivity from 59.9-170 Ωm, 78.5-225 Ωm and 91.0-236 Ωm... Keywords: slip surface, Schlumberger, Geolistrik